Information systems and the internet - Laudon, Kenneth C. (Dryden, 1998)
The book describes and explores the role of information systems in contemporary businesses; provides the technical foundation for inderstanding information system technologies and the Internet; analyzes and designs solutions to problems faced by businesses and other organizations; and provides a more extensive introduction to real-world information systems in organizations